In Silico Study of Vacuolin-1 as an Inhibitor of HSP27 for Precancerous Treatment of Breast Cancer - Agustin, Diah Eka; Ulfah, Mumtaz Nabila; Aisyah, Siti Nur; Arumsari, Pamuji Lestari; Pertiwi, Kadita Octavia; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
Breast cancer has a great chance of being cured if it is diagnosed and treated properly in its early stage. The pre-cancer stage is an early stage of cancer development characterized by the overexpression of HSP27. Therefore, HSP27 can be a therapeutic target of cancer. This study aims to analyze whether vacuolin-1, a small drug compound known for its ability to inhibit metastasis, can inhibit HSP27 to prevent precancerous development in breast cancer, as well as its ADME and biosafety aspects. Protein & ligand structures were obtained from RCSB PDB and PubChem database. Preparation was performed with Discovery Studio and PyRx. Drug-likeness/ADME analysis was performed in Swiss-ADME web server. Biosafety analysis was performed in MetaTox web server. Molecular docking was performed using PyRx. The visualization of docking results was performed using Discovery Studio. The docking result between vacuolin-1 and HSP27 showed that vacuolin-1 can act as an HSP27 inhibitor by interacting with S78 residue of HSP27 and blocking its phosphorylation as well as depolymerization process. The drug-likeness characterization result of this compound showed that vacuolin-1 violates one of the four Lipinski's Rule of Five. Biosafety analysis showed that vacuolin-1 has a low toxicity level with an estimated LD50 around 13,016.65 mg/kg.